Musical education in Hungary - Sandor, Frigyes (Budapest Corvina Press, 1966)
"This volume consists of nine studies which together presents an overall picture of the development and achievements of Hungarian musical education in the last two decades...." Frigyes Sándor violinist, conductor and professor of violin was born as the third child of a civil family. All three children chose music as a career and gained considerable success in that.